2019
DOI: 10.1093/ejcts/ezz266
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, aetiology and outcomes of major postoperative haemorrhage after pulmonary lobectomy

Abstract: OBJECTIVES Post-lobectomy bleeding is uncommon and rarely studied. In this study, we aimed to determine the incidence of post-lobectomy haemorrhage and compare the outcomes of reoperation and non-operative management. METHODS We conducted a single-institution review of lobectomy cases from 2009 to 2018. The patients were divided into two groups based on the treatment for postoperative bleeding: reoperation or transfusion of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 27 publications
0
10
0
1
Order By: Relevance
“…The incidence of unplanned reoperation is 0.53% in our study, which is higher than the published 0.27% (after lung cancer surgeries) [ 8 ], probably due to the included benign tumors herein. Indeed, the benign tumors were reported to be more risky to postoperative bleedings than the malignant tumor, potentially due to inflammation [ 11 ]. Among the initial surgeries caused reoperations, lobectomy plus segmentectomy is the most risky probably due to more complicated manipulations and more bronchus stumps.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of unplanned reoperation is 0.53% in our study, which is higher than the published 0.27% (after lung cancer surgeries) [ 8 ], probably due to the included benign tumors herein. Indeed, the benign tumors were reported to be more risky to postoperative bleedings than the malignant tumor, potentially due to inflammation [ 11 ]. Among the initial surgeries caused reoperations, lobectomy plus segmentectomy is the most risky probably due to more complicated manipulations and more bronchus stumps.…”
Section: Discussionmentioning
confidence: 99%
“…Postoperative bleeding after lung resection is a rare complication, but in cases where it occurs, the chest wall is the most commonly reported bleeding site [1,2]. Typically, bleeding stems from injury to intercostal arteries and can be caused by surgical staples [2].…”
Section: Discussionmentioning
confidence: 99%
“…Postoperative bleeding is a rare, but serious complication. Previous studies have reported that bleeding occurred after pulmonary lobectomy in 2.1% of cases, and surgical materials, such as staples, can be the cause [1,2]. However, a postoperative hemorrhage caused by sutures is rare.…”
Section: Introductionmentioning
confidence: 99%
“…Post lobectomy haemorrhage is rare but most common indication for reoperation. In a recent single centre retrospective review [44], out of 1960 lobectomies, haemorrhage occurred in 2.1% cases, leading to reoperation in 1.4% and non-operative management in 0.8% cases. The median time for reoperation was 17 hours.…”
Section: Haemorrhagementioning
confidence: 99%